Modulation of Motor Cortex Activity After Intrathecal Baclofen Delivery in Chronic Thoracic Spinal Cord Injury - Štětkářová, Ivana; Keller, Jiří (Frontiers in Neurology, 2022)
Objectives: Intrathecal baclofen (ITB) is commonly used for reduction of spasticity in chronic spinal cord injury (SCI). Its clinical effect is well known; however, the exact mechanisms of long-term effect of continuous ITB administration (cITBa) on modulation of cortical processes has not been elucidated. The aim of this study was to evaluate changes of motor cortex activation for healthy upper limbs in comparison to impaired lower limbs using functional magnetic resonance imaging (fMRI). Methods: Ten subjects (8 males, 20-69 years) with thoracic SCI presenting no voluntary movements on lower limbs (except one) were enrolled in fMRI study. 1.5T fMRI with a finger tapping paradigm and mental movement simulating foot flexion on the dominant side were performed before, 3 months and one year after start of cITBa. FMRI data processing was carried out using FEAT, part of FSL. Second-level analysis was carried out using FLAME stage 1 and 2. The level of spasticity was assessed by the Modified Ashworth scale (MAS). Results: Continuous ITB significantly decreased limb spasticity in all subjects (group MAS spasticity dropped from 3 to 0.3). Second-level analysis (Z>1.6, cluster significance threshold p=0.05) revealed increased activation of the primary sensorimotor cortex of the foot between baseline and 3 months, and 3 months and one year, respectively. Conclusion: Increased sensorimotor cortex activation after cITBa with spasticity reduction may reflect distant functional reorganization due to long-term mediated neuroplastic changes of the sensorimotor cortex. Better understanding of modulation of brain function in SCI after cITBa may influence the fields of neurorehabilitation.